Study Protocol for the Hand OsteoArthritis Self-Management and Integrated Scheme (OASIS-H) to Improve Outcomes in Patients with Hand Osteoarthritis—an Open-Label Randomized Controlled Trial - Iris Yan Ki Tang; Lai Man Tang; Brian Ho; Joyce Wong; Amanda Lau; Suet Kei Kwok; Carmen Tze Kwan Ho (Journal of Clinical Rheumatology and Immunology)
The increasing prevalence of hand osteoarthritis (OA) in Hong Kong’s aging population and its economic burden necessitate more effective management strategies. This study examines the efficacy of the Hand OsteoArthritis Self-management and Integrated Scheme (OASIS-H) compared to routine clinical care for patients with symptomatic hand OA. In this open-label, randomized controlled trial, symptomatic OA hand patients are included and randomized into early intervention and routine clinical care groups. The early intervention group undergoes an 8-week integrated hand OA management program, consisting of modified self-management education sessions, exercise, education, and occupational therapy intervention. At 6 months, routine clinical care patients will cross over to receive the same program as the early intervention group. The primary endpoint is the change in finger pain on visual analogue scale (VAS) at 6 months from baseline. The study aims to determine if the integrated program is more efficacious than routine care in reducing pain and improving function in hand OA patients.